2014
DOI: 10.4085/1062-6050.49.3.45
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Shortwave Diathermy and Joint Mobilizations for Achieving Normal Elbow Range of Motion After Injury or Surgery With Implanted Metal: A Case Series

Abstract: Context: Regaining full, active range of motion (ROM) after trauma to the elbow is difficult.Objective: To report the cases of 6 patients who lacked full ROM in the elbow because of trauma. The treatment regimen was thermal pulsed shortwave diathermy and joint mobilizations.Design Intervention(s): Treatment consisted of 20 minutes of pulsed shortwave diathermy at 800 pulses per second for 400 microseconds (40-48 W average power, 150 W peak power) applied to the cubital fossa, immediately followed by 7 to 8 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Similar studies involving only SWT that were conducted on either asymptomatic subjects (12,14,15,31) or patient groups (10,32,33) have been reported previously. However, to our knowledge this will be the first in vivo study that investigated the deep physiological responses to RF exposure below the shortwave frequency band.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similar studies involving only SWT that were conducted on either asymptomatic subjects (12,14,15,31) or patient groups (10,32,33) have been reported previously. However, to our knowledge this will be the first in vivo study that investigated the deep physiological responses to RF exposure below the shortwave frequency band.…”
Section: Introductionsupporting
confidence: 64%
“…Increasing muscle blood flow may potentially aid faster recovery from post exercise fatigue. In physiotherapy, radiofrequency (RF)-based EPAs are among those that claim to increase blood flow as well as improve soft tissue compliance, mainly by inducing tissue hyperthermia (9)(10)(11)(12)(13)(14)(15). Measures relating to blood flow and tissue compliance closely reflect the body's response when tissues are exposed to heat, with the radiofrequency energy potentially capable of inducing a hyperthermic effect at depth (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…pSWD was reported to be effective also for treatment of chronic low back pain (Ahmed et al 2009) and in entrapment neuropathies, such as carpal tunnel syndrome (Incebiyik et al 2015). The combination of thermal pulsed short-wave diathermy and joint mobilizations was effective in restoring active range of motion (ROM) of elbow extension in patients who lacked full ROM after injury or surgery (Draper 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Applying TT alone on a MG latent MTP does not produce changes in ROM when it is measured with the lunge test. On the other hand, Draper et al reported that the combination of TT and joint mobilization is considered to be an effective treatment to recover joint ROM in elbow extension in post-surgical patients [47].…”
Section: Discussionmentioning
confidence: 99%